On C-Left Hyperideals of Ordered Semihypergroups (Communications in Mathematical Research, 2019)
In this paper, the concept of C-left hyperideals is introduced in orderedsemihypergroups, and several related properties are investigated. In particular, wediscuss the relationships between the greatest left hyperideals and C-left hyperidealsof ordered semihypergroups. Furthermore, we introduce the concept of left basesof an ordered semihypergroup, and give out the sufficient and necessary conditionsof the existence of the greatest C-left hyperideal of an ordered semihypergroup bythe properties of left bases. The result about C-left ideals in ordered semigroups isgeneralized to the ordered semihypergroups.